Protective effect of Moringa oleifera leaves extract on cardiac fibrosis of streptozotocin-induced diabetic rats - Salsabila, Zadia Maheswari; Suryono, .; Pralampita, Pulong Wijang (Universitas Gadjah Mada, 2023)
Diabetes mellitus (DM) is a metabolic disease characterized by chronic hyperglycemia that induces excessive reactive oxygen species (ROS) production and causes oxidative stress. Diabetic cardiomyopathy is a diabetic complication characterized by structural and functional changes of the myocardium. Fibrosis is one of the pathological features of diabetic cardiomyopathy. Moringa oleifera leaves have been reported to possess antidiabetic and antioxidant activities which could prevent diabetic complications such as cardiomyopathy. A previous study reported that M. oleifera leaves extract have protective effects to the kidneys and liver of rats exposed to oxidative stress. This study aimed to investigate the protective effect of the M. oleifera leaves extract on cardiac fibrosis of rats induced by streptozotocin (STZ). This was an experimental study using a posttest-only control group design. Thirty-three male Wistar rats were randomly divided into three groups i.e. normal control group (Group 1) were administered normal saline, diabetic control group (Group 2) were administered normal saline, and diabetic treatment group (Group 3) were administered M. oleifera leaves extract. Diabetes induction of rats was conducted by intraperitoneally injection of STZ at dose of 45 mg/kg BW. The M. oleifera leaves extract at a dose of 1000 mg/kg BW was administered orally one time a day for 28 days. Statistical analysis was performed using the Kruskal-Wallis test followed by Mann Whitney. A significant difference in cardiac fibrosis occurrence between three groups was observed (p < 0.05). No cardiac fibrosis was observed in normal control group, meanwhile cardiac fibrosis was observed in all rats (9 rats) of the diabetic control group (G2). Only 2 rats in the treatment group (G3) had cardiac fibrosis. In conclusion, M. oleifera leaves extract can inhibit cardiac fibrosis in STZ-induced diabetic rats.